Abscess of Cavum Septum Pellucidum Complicating Pneumococcal Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
A 7-year-old boy with pneumococcal meningitis complicated by abscesses involving the cavum septum pellucidum (CSP) and cavum vergae (CV) is reported from the Children's Hospital and University of California San Diego, CA.